Older people's willingness to delay social security claiming - Raimond Maurer; Olivia S. Mitchell (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
We designed and fielded an experimental module in the 2014 HRS which seeks to measure older persons' willingness to voluntarily defer claiming of Social Security benefits. In addition we evaluate the stated willingness of older individuals to work longer, depending on the Social Security incentives offered to delay claiming their benefits. Our project extends previous work by analyzing the results from our HRS module and comparing findings from other data sources, which included very much smaller samples of older persons. We show that half of the respondents would delay claiming if no work requirement were in place under the status quo, and only slightly fewer, 46 percent, with a work requirement. We also asked respondents how large a lump sum they would need with or without a work requirement. In the former case, the average amount needed to induce delayed claiming was about 60,400, while when part-time work was required, the average was 66,700. This implies a low utility value of leisure foregone of only 6,300, or about 10 percent of older households' income.
urn:nbn:de:hebis:30:3-441534
Keywords: 330